Chrysanthemum Production in Bangladesh: Significance the Insect Pests and Diseases Management: A Review - Ahasan Ullah Khan; Md Abdur Razzak Choudhury; Anayat Ullah Khan; Saugat Khanal; Abu Rashed Md Maukeeb (Journal of Multidisciplinary Applied Natural Science, 2021)
Chrysanthemum is a floricultural, ornamental and medicinal plant with tremendous income cash crop which is cultivated chiefly in winter. The crop charity as nerve sedative, anti-oxidant, anti-inflammatory, anti-mutagenic, anti-microbial, anti-fungal, anti-angiogenic, anti-atherosclerosis and nematocidal goods. Chrysanthemum has been used for hundreds of years in manufacturing medicine. It is used to treat respiratory complications, high blood pressure, and hyperthyroidism and reduce inflammation. Leaves remedies for colds, headaches, bronchitis, rheumatism, and swellings. The plant has aesthetic significance as well. Nevertheless, outbreaks of pests and diseases have hold back Chrysanthemum cultivation in Bangladesh. Insect pest damages the plant directly by sucking cell sap and indirectly spread out of virus diseases as act of vector. Aphid resistance variety might be the effective tool for successful production of chrysanthemum plant. Sustainable crop disease management for Chrysanthemum needs a multitude of consideration of the impacts of management methods on economics, sociology and ecology by wholly understanding the mechanisms of crop disease epidemics and the functioning of normal agroecosystems. The findings of this study present clear insights into efforts that will encourage farmers to adopt effective and ecological methods of pest and disease management for successful chrysanthemum production in Bangladesh.